Host-Brucella interactions and the Brucella genome as tools for subunit antigen discovery and immunization against brucellosis - Gomez, Gabriel; Adams, Leslie G.; Ficht, Allison R.; Ficht, Thomas A. (Frontiers in Cellular and Infection Microbiology, 2013)
Vaccination is the most important approach to counteract infectious diseases. Thus, the development of new and improved vaccines for existing, emerging and re-emerging diseases is an area of great interest to the scientific community and general public. Traditional approaches to subunit antigen discovery and vaccine development lack consideration for the critical vaccination aspects of public safety and activation of relevant protective host immunity. The availability of genomic sequences for Brucella and other important pathogens and their hosts have led to development of systems-wide analytical tools that have provided a better understanding of host and pathogen physiology while also beginning to unravel the intricacies at the host-pathogen interface. Advances in pathogen biology, host immunology, and host-agent interactions have the potential to serve as platform for the design and implementation of better-targeted antigen discovery approaches. With emphasis on Brucella, we probe biological aspects of host and pathogen that merit consideration in the targeted design of subunit antigen discovery and vaccine development.